Development of Augmented Reality-Based High School Physics Learning Media on Static Electricity Material - Fadhilah, Khairunnisa Hayatul; Haryanto, Zeni; Komariyah, Laili (Department of Physics Education, Universitas Mataram, 2024)
Physics is a branch of science that discusses natural phenomena. Physics learning process is expected to facilitate students to observe the phenomenon directly, but not all phenomena can be observed directly. One of them is static electricity subject material. So, learning media is needed that can channel information to students. Teachers can create various learning media with dynamic representations such as Augmented Reality. This study aims to determine the feasibility of Augmented Reality based learning media on static electricity material developed. This research is a type of R & D (Research and Development) research with the 4D model (Define, Design, Development, and Disseminate). The media feasibility test is determined through validation by 4 validators, namely 2 media experts and 2 material experts. The results of the feasibility test in terms of media with indicators of graphics and language got a percentage of 81% with very feasible criteria and in terms of material with content, presentation, and contextual indicators of 83% with very feasible criteria. Thus the development of Augmented Reality-based learning media on static electricity material is very feasible to use in supporting physics learning. Keywords: Learning Media; Augmented Reality; 4D; Feasibility Test.